Soft ξ-open sets in Soft Topological Spaces - Mohammed, Ramadhan A.; Ameen, Ramziya S. (Science Journal of University of Zakho, 2019)
The objective of studing the current paper is to introduced a new class of soft open sets in soft topological spaces called soft -open sets. Then soft -open sets are used to study some soft topological concepts. Furthermore, the concept of soft -continuous and almost soft -continuous functions are defined by using the soft -open sets. Some properties and Characterizations of such functions are given.